George W. Bush's healthy forests : reframing the environmental debate - Switzer, Jacqueline Vaughn (University Press of Colorado, 2005)
The authors detail Bush administration reframing of America's environmental debate, identifying players, events, and strategies that expedited a policy shift that impacts public lands and long-standing avenues of public involvement.